If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 25 + -1x = 45 + 6x Solving 25 + -1x = 45 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 25 + -1x + -6x = 45 + 6x + -6x Combine like terms: -1x + -6x = -7x 25 + -7x = 45 + 6x + -6x Combine like terms: 6x + -6x = 0 25 + -7x = 45 + 0 25 + -7x = 45 Add '-25' to each side of the equation. 25 + -25 + -7x = 45 + -25 Combine like terms: 25 + -25 = 0 0 + -7x = 45 + -25 -7x = 45 + -25 Combine like terms: 45 + -25 = 20 -7x = 20 Divide each side by '-7'. x = -2.857142857 Simplifying x = -2.857142857
| (-2.2)(1.5)(-4.2)= | | 4(2x-1)=9 | | =x^2-8x+63 | | 3-5b=7-3b | | .4x+8.5=.65(x+10) | | =x^2-8x+67 | | y+6=-4(x+4) | | =x^2-10x+98 | | 9-x=12-5x | | 5x^2+30-60=0 | | 5x^2+1-246=0 | | 5(x+y)=zforx | | 9-c=12-5c | | f(x)=x^2-10x+98 | | 5x^2+26-24=0 | | Y=8/9x-4 | | 9x-1=107 | | x^3+3x-2=0 | | 7[4-(3-5x)]+x=4(9x+2)-1 | | -10x+3(x-4)+6x=5x-48 | | 2-6=36x-5 | | x-2+x+3=3x-4 | | x(5x+7)=2x^2-9x+64 | | 15x-60=-12x-54 | | -[4z-(9z+8)]=8+(4z+6) | | 3x^9/2x^5 | | 10+6r=104 | | 8a-2a+12=10a-4 | | 10-6r=104 | | 10a-22=13a+5 | | 15=6-2a | | 7+1=7x-11 |